2009
DOI: 10.1007/s00477-009-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate changes and their impacts on water resources in the arid regions: a case study of the Tarim River basin, China

Abstract: Streamflow series of five hydrological stations were analyzed with aim to indicate variability of water resources in the Tarim River basin. Besides, impacts of climate changes on water resources were investigated by analyzing daily precipitation and temperature data of 23 meteorological stations covering 1960-2005. Some interesting and important results were obtained: (1) the study region is characterized by increasing temperature, however, only temperature in autumn is in significant increasing trend; (2) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(68 citation statements)
references
References 28 publications
2
65
0
1
Order By: Relevance
“…Previous studies also indicated that the increase of annual runoff of these two catchments was caused by increases in temperature and precipitation, based on correlations between runoff time series of the Kakshaal and Sari-Djaz catchments with precipitation and temperature time series of meteorological stations Zhang et al, 2010], but did not quantify the role of precipitation or temperature increases. Based on a hydrological simulation approach, a study by Zhao et al [2013] found that discharge increases over the period 1970-2007 were (a) due to precipitation increases alone in the Kakshaal catchment and (b) by 96% due to increases in precipitation and 4% due to increases in glacier melt in the Sari-Djaz catchment.…”
Section: Glacier Melt Contribution and Trend Attribution For Two Headmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies also indicated that the increase of annual runoff of these two catchments was caused by increases in temperature and precipitation, based on correlations between runoff time series of the Kakshaal and Sari-Djaz catchments with precipitation and temperature time series of meteorological stations Zhang et al, 2010], but did not quantify the role of precipitation or temperature increases. Based on a hydrological simulation approach, a study by Zhao et al [2013] found that discharge increases over the period 1970-2007 were (a) due to precipitation increases alone in the Kakshaal catchment and (b) by 96% due to increases in precipitation and 4% due to increases in glacier melt in the Sari-Djaz catchment.…”
Section: Glacier Melt Contribution and Trend Attribution For Two Headmentioning
confidence: 96%
“…Several studies report increasing discharge of the Aksu headwater streams over the period 1957-2004[e.g., Zhang et al, 2010Krysanova et al, 2014]. While it is assumed that these increases are related to concurrent trends in temperature and precipitation [Chen et al, 2009;Xu et al, 2010;Zhang et al, 2010;Tao et al, 2011], a thorough attribution analysis is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…changes in streamflows, snowmelt timing) are most commonly examined to investigate the impact of climate change on water resources (e.g. Cayan et al 2008;Siliverstovs et al 2009;Zhang et al 2009). To relate lake warming trend with climate change, shifts in trends of air temperature, snowfall percent to total precipitations, and snow melt timing in the basin are examined.…”
Section: Introductionmentioning
confidence: 99%
“…O teste de Mann-Kendall e o teste t do coeficiente angular da equação de regressão são os testes mais utilizados para a verificação de presença de tendência em séries de dados (RODERICK & FARQUHAR, 2005), (WANG et al, 2006) (ZHANG et al, 2010). (XU et al, 2006a).…”
Section: Análise De Tendênciaunclassified